Elaboração de um modelo de valoração quantitativa das garantias para o setor de saneamento com utilização de Simulação de Monte Carlo: o caso PPP de Esgoto para a Região Metropolitana do Recife e Município de Goiânia - Albuquerque, Guilherme da Rocha (2014)
The sanitation situation in Brazil is alarming. Water supply and sewage services are provided appropriately for only 59.4% and 39.7%, respectively, of the Brazilian population. It is estimated that R$ 304 billion in investments are needed to change this situation. Part of this amount will come from the private sector and the structuring of public-private partnerships is one way to achieve this goal. In order to ensure economic viability of this type of project it is common for the public sector to provide guarantees to the private partner. This paper presents a model for the valuation of these guarantees, using as case studies the PPP of sewage services from the metropolitan region of Recife and the city of Goiana. The result evidenced the importance of this valuation, since depending on the level of security offered to the private sector, the expected present value of the public sector disbursements ranged from zero to R$ 204 million.